2000
DOI: 10.1136/adc.83.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral glucocorticoid treatment on serum inflammatory markers in acute asthma

Abstract: Background-Acute asthma is associated with elevated serum concentrations of products of activated T cells and eosinophils. Aims-To compare the changes in concentrations of these products with disease severity and changes in lung function following oral prednisolone treatment. Methods-Twenty patients (mean age 8.7 years) were recruited on admission with acute asthma to a district general hospital. Disease severity was recorded before and after treatment with oral prednisolone using a validated pulmonary index s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
2
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 15 publications
2
32
2
3
Order By: Relevance
“…Despite the administration of oral prednisolone for 5 days to children with acute asthma, FENO was still elevated, implying residual inflammation [69,71]. A similar finding was reported in a study measuring interleukin (IL)-5, sIL2R, and ECP [137]. Future research in exhaled NO in children should try to determine the onset of anti-inflammatory effects and the time of maximum anti-inflammatory effects of existing and new anti-asthma medications.…”
Section: Future Research: the Important Questionssupporting
confidence: 59%
“…Despite the administration of oral prednisolone for 5 days to children with acute asthma, FENO was still elevated, implying residual inflammation [69,71]. A similar finding was reported in a study measuring interleukin (IL)-5, sIL2R, and ECP [137]. Future research in exhaled NO in children should try to determine the onset of anti-inflammatory effects and the time of maximum anti-inflammatory effects of existing and new anti-asthma medications.…”
Section: Future Research: the Important Questionssupporting
confidence: 59%
“…In this study, treatment comprising systemic corticosteroids resulted in decreases in serum levels of ECP, IL-5, IL-6, IL-1ra and IP-10, but not IL-8, IL-10, G-CSF and MCP-1. In previous studies, systemic corticosteroid treatment of children with asthma significantly reduced serum concentrations of ECP [24,25,26], IL-5 [26] and IP-10 [12]. Furthermore, systemic corticosteroids significantly reduced both IL-5 gene expression and serum levels of ECP in acute compared with stable asthma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial biochemical effects appear in an acute asthma case after oral corticoid is administered, such as reduced serum interleukin 5 levels, interleukin-2(CD25) receptor levels and eosinophil cationic protein levels. 3 Studies of inhaled corticoid during asthma exacerbation have returned conflicting results as a result of varying doses and medications and also of differing study designs and outcomes, which impedes adequate comparison. An interesting approach suggests that budesonide could be an effective adjunct to prednisone for infants with acute asthma, 10 but as it implies increased costs the true benefit must be better analyzed.…”
Section: See Related Article On Page 106mentioning
confidence: 99%
“…Overall, the significant biological actions performed by this group of medications in acute asthma are: the suppression of the synthesis of Th2 cytokines such as IL-5 thus reducing eosinophilic infiltration into the airways, the reduction of plasma exudation with consequent mucus secretion, and the reduction of inflammatory mediators such as leukotrienes and prostaglandins. 3 Inhaled steroids have greater anti-asthmatic potential and anti-inflammatory power than do oral steroids and can offer rapid results during a crises since they act directly on the lungs. This being the case, the following research question is posed: Could inhaled steroids be indicated for acute asthma?.…”
mentioning
confidence: 99%